Acetylene hydrochlorination over 13X zeolite catalysts at high temperature. Issue 22 (13th October 2016) - Song, Zhijia; Liu, Guangye; He, Dawei; Pang, Xiaodong; Tong, Yansi; Wu, Yaqi; Yuan, Danhua; Liu, Zhongmin; Xu, Yunpeng
Abstract : 13X zeolite exhibited high catalytic activity in acetylene hydrochlorination at high temperatures. Abstract : 13X zeolite exhibited high catalytic activity and selectivity in acetylene hydrochlorination at high temperatures above 300 °C. The activity of 13X may be derived from its unique zeolite structure, meanwhile Na + and the active carbon deposit facilitated acetylene hydrochlorination. This finding presented a promising approach for the development of green non-mercury catalysts.